Exploring the Interplay of E-Readiness, Technical Skills, and Digital Resources on Digital Literacy of Business Students: A Two-Stage PLS-ANN Approach - Karmacharya, Bibek (Journal of Business and Management, 2024)
Background: Digital literacy has emerged as a key skill for success in today’s quickly evolving digital world, especially in the field of business education, where students must be able to use digital tools and technologies effectively in order to succeed in both their academic and professional endeavours. Objectives: This study intends to explore the relationship between digital literacy and e-readiness among Pokhara University’s Bachelor of Business Administration (BBA) and Master of Business Administration (MBA) students. It focuses on the ways that institutional support, technical proficiency, and access to digital resources affect the development of digital literacy skills. Methods: A causal-comparative research design was used to examine the impact of e-readiness, technical skills, and digital resource access on digital literacy among 360 BBA and MBA students at Pokhara University. Data were analyzed using Structural Equation Modeling (SEM) via Smart PLS and Artificial Neural Networks (ANN), with SEM identifying significant relationships and ANN assessing the predictive importance of each factor. Results: SEM revealed that e-readiness, technical skills, and resource access significantly affect digital literacy, with technical skills being the strongest predictor. ANN confirmed the critical role of e-readiness and supportive learning environments, with digital resource availability being the least influential. Conclusion: The findings emphasize the need for integrating technical skills training and improving resource accessibility into curricula to enhance digital literacy. Supportive environments and technical competencies are essential for students’ digital proficiency. JEL Classification: D83, I23, L86, O33